Germline mutation in DOK7 associated with fetal akinesia deformation sequence. - Vogt, J; Morgan, N; Marton, T; Maxwell, S; Harrison, B; Beeson, D; Maher, E (2009)
BACKGROUND: Fetal akinesia deformation sequence syndrome (FADS) is a heterogeneous disorder characterised by fetal akinesia and developmental defects including, in some case, pterygia. Multiple pterygium syndromes (MPS) are traditionally divided into prenatally lethal and non-lethal (such as Escobar) types. Previously, we and others reported that homozygous mutations in the fetal acetylcholine receptor gamma subunit (CHRNG) can cause both lethal and non-lethal MPS, demonstrating that pterygia resulted from fetal akinesia, and that mutations in the acetylcholine receptor subunits CHRNA1, CHRND, and Rapsyn (RAPSN) can also result in a MPS/FADS phenotype. METHODS: We hypothesised that mutations in other acetylcholine receptor related genes may interfere with neurotransmission at the neuromuscular junction and so we analysed 14 cases of lethal MPS/FADS without CHRNG, CHRNA1, CHRNB1, CHRND, or RAPSN mutations for mutations in DOK7. RESULTS: A homozygous DOK7 splice site mutation, c.331+1G>T, was identified in a family with three children affected with lethal FADS. Previously DOK7 mutations have been reported to underlie a congenital myaesthenic syndrome with a characteristic "limb girdle" pattern of muscle weakness. CONCLUSION: This finding is consistent with the hypothesis that whereas incomplete loss of DOK7 function may cause congenital myasthenia, more severe loss of function can result in a lethal fetal akinesia phenotype.